Integrated scFv identification and CAR T cell generation for AML targeting in vivo - Liu, Yi; Lauk, Annika; Sedloev, David; Brysting, Josephine; Cetin, Ela; Liu, Chunan; Mönnig, Maximilian; Luft, Thomas; Yun, Haiyang; Schmitt, Michael; Sauer, Tim; Zhou, Fengbiao; et al. (International journal of cancer, 2026)
Cancer immunotherapy has witnessed remarkable advancements, particularly in the development of chimeric antigen receptor (CAR) T cell therapy. Here, we integrated single chain variable fragment (scFv) development with CAR T cell generation based on a newly developed scFv phagemid library. High-throughput long-read PacBio sequencing identified 4.5 × 107 unique full-length scFv proteins within the generated library. As a proof of principle, we screened for scFvs targeting C-type lectin-like molecule-1 (CLL1) with subsequent cloning into a third generation retroviral CAR backbone. Functional assays revealed the specificity and potency of these CAR T cells in targeting CLL1-positive AML cells in vitro. In vivo studies reduced tumor burden and improved survival rates compared to controls. Taken together, screening for tumor-specific scFvs against CLL1 can rapidly generate AML-specific CAR T cells with effective tumor killing in vivo.
Online verfügbar am 2. Oktober 2025
Gesehen am 27.01.2026